2006
DOI: 10.1002/ppul.20500
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training in Morquio's syndrome: A case study

Abstract: We reported a case of MPS IV A presented with dyspnea on exertion and respiratory muscle weakness. The patient underwent inspiratory muscle training (IMT) using threshold loading for 18 weeks. After 6 weeks of initial IMT, aerobic exercise training consisting of walking was added to the treatment program. Inspiratory muscle strength increased 70%, and 6-minute walk test (6MWT) distance increased to 47 m. With the inclusion of aerobic exercise training, additional increases in inspiratory muscle strength (7%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…In these cases, hypoxic and hypercapnic (type 2) respiratory failure and respiratory muscle weakness may occur. Savcı et al (6) reported that respiratory muscle weakness in patients with Morquio syndrome is caused by metabolic abnormalities, wall deformities, and the muscles' not being used. In our case, hypoxemia and hypercapnia caused by kyphoscoliosis, pectus carinatum deformity, and respiratory muscle weakness were also present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, hypoxic and hypercapnic (type 2) respiratory failure and respiratory muscle weakness may occur. Savcı et al (6) reported that respiratory muscle weakness in patients with Morquio syndrome is caused by metabolic abnormalities, wall deformities, and the muscles' not being used. In our case, hypoxemia and hypercapnia caused by kyphoscoliosis, pectus carinatum deformity, and respiratory muscle weakness were also present.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory problems observed in Morquio syndrome contain restrictive-type respiratory failures caused by thoracic deformities and respiratory muscle weakness. Another reason for the respiratory problems in these patients is obstructive sleep apnea syndrome (OSAS) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…1.097 üniversite öğrencisi üze-rinde yaptıkları çalışmada, BKİ değeri 25 kg/m 2 'nin üzerinde ve altında olan bireylerin fiziksel aktivite düzeyleri arasında anlamlı fark olmadığını belirtmişlerdir. 4 Jimenez-Pavon ve ark., şiddetli fiziksel aktivite ile yağ kütlesi indekslerinin negatif, kas kütlesinin ise pozitif ilişkili olduğunu göstermiş-lerdir. 26 Çalışmamızda da fiziksel aktivite ile BKİ arasında ilişki saptanmamıştır.…”
Section: Gereç Ve Yöntemlerunclassified
“…Savcı ve ark., 2006 yılında Türkiye'de yaptıkları çalışmada, üniversite öğrencilerinin sadece %18'inin yeterli fiziksel aktiviteye, %68'inin ise düşük fiziksel aktivite düzeyine sahip olduğunu belirtmişlerdir. 4 Ayrıca çalışmalarda; düzenli fiziksel aktivitenin, özellikle kardiyovasküler hastalık-lar ve metabolik sendrom gibi sağlığı etkileyen risk faktörlerini önemli derecede azalttığı ve ortalama yaşam süresini yaklaşık 2-4 yıl artırdığı rapor edilmiştir. 1,5 Denge, destek yüzeyi içerisinde vücut kütle merkezinin kontrol edilebilme becerisi olarak adlandırılmaktadır.…”
unclassified
“…Health related behaviors acquired in the early period of life effect risks of life style related disorders which can occur in the later period. In this respect, research on health behaviors of young people is important [7,8].…”
Section: Introductionmentioning
confidence: 99%